The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.psj.2020.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat bran in comparison to antibiotics on growth performance, intestinal immunity, barrier function, and microbial composition in broiler chickens

Abstract: This experiment was conducted to evaluate the effects of wheat bran ( WB ) and antibiotics on growth performance, intestinal immunity, barrier function, and microbial composition in broiler chickens. A total of 168 one-day-old male Arbor Acre chicks were allocated to 3 treatments consisting of 7 replicates with 8 birds per replicate. The 3 treatments were: an antibiotic-free control diet (control, CON), CON + 75 mg/kg chlortetracycline as an antibiotic growth promoter ( AGP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 53 publications
0
29
0
5
Order By: Relevance
“…Meanwhile, as a vital index of immune function to some extent, antioxidant function is closely related to immune function ( Min et al., 2016 ). sIgA was secreted by animal plasma cells and was the most prominent antibody presented in mucosal surfaces and protected intestinal mucosa against invading pathogens in the gastrointestinal tract ( Shang et al., 2020 ). However, limited studies have been conducted to evaluate the effects of OEO on broiler intestinal mucosa sIgA content.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, as a vital index of immune function to some extent, antioxidant function is closely related to immune function ( Min et al., 2016 ). sIgA was secreted by animal plasma cells and was the most prominent antibody presented in mucosal surfaces and protected intestinal mucosa against invading pathogens in the gastrointestinal tract ( Shang et al., 2020 ). However, limited studies have been conducted to evaluate the effects of OEO on broiler intestinal mucosa sIgA content.…”
Section: Discussionmentioning
confidence: 99%
“…Clostridium butyricum seems to be a promising probiotic to provide protection against intestinal infections [11], and some reports show beneficial effects of C. butyricum strains on growth performance, lipid metabolism, immune function and culturable microbiota [12,13]. Although wheat bran and C. butyricum supplementations have been investigated from various aspects in broilers at slaughter age, little information is available on the effects of wheat bran using culture-independent methods [5,[14][15][16]. The information concerning C. butyricum is limited only to culturable microbiota in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal barrier acts as the first line of defence against bacteria and virus infections. Numerous studies in the livestock field have demonstrated that growth performance is closely and positively associated with intestinal barrier functions ( Koo et al., 2020 ; Shang et al., 2020 ; Shi et al., 2020 ; Xiang et al., 2020 ), affirming intact intestinal barrier function as a crucial factor determining animals' health and growth performance. Under the severe challenges by in-feed antibiotic prohibition and African swine fever prevalence in China, it is crucial to effectively and at low cost, screen feed additives for protecting the porcine intestinal barrier against various damage induced by adverse factors, such as early weaning stress, mycotoxin-contaminated feed, and pathogens infection.…”
Section: Discussionmentioning
confidence: 99%